Reasons behind flu vaccine acceptance and suggested interventions to promote flu vaccination acceptance among healthcare workers. Issue 3 (May 2021) - Santangelo, Omar Enzo; Cedrone, Fabrizio; Gentile, Leandro; Provenzano, Sandro; Dallagiacoma, Giulia; Armetta, Francesco; Gianfredi, Vincenza
The flu vaccination rate is still too low, both among healthcare providers (HCPs) and among health sciences university students. This study aims to assess the reasons of past and future flu vaccination acceptance among health sciences university students, and second, to identify what interventions would be helpful to foster acceptance of the flu vaccination among HCPs. A multicentre cross-sectional study was performed, using a validated questionnaire administered to health sciences students enrolled in 14 Italian universities. A multivariable logistic regression model was used. A total of 3131 questionnaires were collected. The statement that mandatory vaccination is required to increase adhesions to vaccinations (adjusted odds ratio [aOR] = 1.57; 95% confidence interval [CI] = 1.25–1.97), being in favour of this obligation (aOR = 7.91; 95% CI = 2.50–25.02) and considering themselves as people at risk of infection (aOR = 1.96; 95% CI = 1.46–2.64), are associated with having received the vaccination in the past flu season; on the other hand, planning to be vaccinated for the next season to avoid infecting patients is protective (aOR = 0.51; 95% CI = 0.38–0.70). This study shows which beliefs are associated with having joined the previous vaccination campaign in a large sample of HCPs. The acceptance of vaccination is an outcome behaviour resulting from a complex decision-making process. In order to implement coverage of the influenza vaccination in HCPs, it is necessary to implement awareness campaigns and provide specific information for this category of workers.